1988
DOI: 10.1002/ijc.2910410204
|View full text |Cite
|
Sign up to set email alerts
|

P53 expression in breast cancer

Abstract: Immunohistochemical evaluation of 200 primary breast cancers with the anti-p53 mouse monoclonal antibody (MAb) PAb421 showed positivity in nuclei of malignant cells in 31 cases (15.5%). PAb421+ cases were significantly more frequently epidermal growth factor receptor (EGF-R)-positive (67.7%; p less than 0.001) and estrogen receptor (ER)-negative (73.3%; p less than 0.001); they displayed surface histocompatibility class-1 (80.6%; p less than 0.01) and 11 (74.2%; p less than 0.05) antigens. Low values for proge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

30
138
3
5

Year Published

1993
1993
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 526 publications
(176 citation statements)
references
References 40 publications
30
138
3
5
Order By: Relevance
“…The proportion of cancers with p53 mutation (20%), p53 allele loss (41%), p53 mRNA expression (54%) and overexpression (28%) or p53 protein expression (32%) are similar to the reported series (Cattoretti et al, 1988;Davidoff, 1991;Iwaya, 1991;Kovach et al, 1991;Osborne et al, 1991;Runnebaum et al, 1991;Varley et al, 1991;Vojtesek et al, 1992;Andersen et al, 1993;Barnes, 1993;Friedrichs, 1993;Martinazzi, 1993;Thorlacius et al, 1993;Tsuda et al, 1993;Marks et al, 1994;Bergh et al, 1995;Borressen et al, 1995;Stenmark-Askmalm et al, 1995).…”
Section: Discussionsupporting
confidence: 74%
“…The proportion of cancers with p53 mutation (20%), p53 allele loss (41%), p53 mRNA expression (54%) and overexpression (28%) or p53 protein expression (32%) are similar to the reported series (Cattoretti et al, 1988;Davidoff, 1991;Iwaya, 1991;Kovach et al, 1991;Osborne et al, 1991;Runnebaum et al, 1991;Varley et al, 1991;Vojtesek et al, 1992;Andersen et al, 1993;Barnes, 1993;Friedrichs, 1993;Martinazzi, 1993;Thorlacius et al, 1993;Tsuda et al, 1993;Marks et al, 1994;Bergh et al, 1995;Borressen et al, 1995;Stenmark-Askmalm et al, 1995).…”
Section: Discussionsupporting
confidence: 74%
“…The identification of nuclear accumulation of p53 protein in 22% of the primary breast carcinomas in the present study is significantly less than the 57% reported by Thompson et al (1990) at the mRNA level, the 54% reported by Bartek et al, (1990a) using PAb 1801, 240, and 421, and the 45% reported by Cattoretti et al (1988) (Crawford et al, 1984;Davidoff et al, 1991b;Thor et al, 1992 (Bartek et al, 1990a). …”
Section: Discussioncontrasting
confidence: 72%
“…Several findings indicate that inactivation of TP53 is associated with a growth advantage in breast carcinoma: Accumulation of p53 protein has been reported to be associated with high grade tumours, increased levels of epidermal growth factor receptor (EGFR), presence of the proliferation associated antigen Ki67, advanced stage, metastatic spread, and low concentrations of oestrogen and progesterone receptors (Cattoretti et al, 1988;Thompson et al, 1990;Davidoff et al, 1991a;Varley et al, 1991;Mazars et al, 1992). Recent reports conclude that positive p53 immunostaining in primary tumour represents a prognostic parameter, suggesting that p53 protein accumulation might become clinically useful as an indicator of breast cancer aggressiveness (Iwaya et al, 1991;Ostrowsky et al, 1991;Varley et al, 1991;Isola et al, 1992;Mazars et al, 1992;Thor et al, 1992).…”
mentioning
confidence: 99%
“…Like Pieteläinen et al (26), we found no correlation between p53 status and histologic grade, whereas two other groups reported higher p53 accumulation rates in poorly differentiated breast carcinomas (25,30). Although p53 is thought to be a determinant of genomic instability (33), we and others (24,26,27,31) did not find an association between abnormal p53 expression and DNA aneuploidy. Such a correlation was, however, described by Jacquemier et al (7).…”
Section: Discussionsupporting
confidence: 51%